Relationship between socioeconomic development and Foreign Franchise presence in north lima - Wong Cabanillas, Francisco Javier (2013)
North Lima is an example of the transformation and socio-economic development based tending a large human capital of men and women who are fully involved in its development not only as entrepreneurs and / or entrepreneurs. At the same time, take into account the different perspectives through which recognize socioeconomic growth and business development in North Lima, which contributes to the presence of franchises in the area in question. Whereby we focus on understand, identify and classify the wealth and potential of North Lima and envision a future both socioeconomic and urban emporium.